Prevalence of Urinary Tract Disorders in Residents of Kahrizak Elderly House - R Khanighaleejogh; M Akbari Kaji; A Shamsi; H Norrighoshki (Tehran University of Medical Sciences, 2011)
Background & Aim: Urinary tract infection is one of the most prevalent complains among elderly in primary care centers. The purpose of this study was to assess urinary tract disorders and prevalence of urinary tract infection in residents of Kahrizak elderly House.Methods & Materials: In this cross-sectional study, 142 men and 114 women (mean age: 76.03±8.32 years) were randomly selected for the study. Data were gathered using a questionnaire. Weight and height of the participants was measured and urine cultures were ordered. Data were analyzed using c2 and Fisher's exact test. The P<0.05 denoted statistical significance.Results: Findings showed that 34% of elderly had urinary tract infection. Of those, 55% (46 cases) were women and 45% (41 cases) were men. Prostate hypertrophy (32.5%) and gyneacologic disorders (16.9%) were the most diagnosed disorders (P<0.05).Conclusion: The prevalence of urine tract infection in elderly with urinary system disorders is high. Recognizing at risk elderly and referring them to the health care centers can prevent urinary tract infection and its complications.